Development of an Android Application for Recipe Management Using Flutter and API - Eko Sutono; Adam Muiz; Muhammad Hafiz Pratama (bit-Tech, 2025)
The advancement of digital technology encourages micro, small, and medium enterprises (MSMEs) to adapt their operational systems, including food recipe management. Many culinary businesses still rely on manual methods, which are prone to data loss, ingredient inconsistency, and inefficiencies. This condition often leads to increased operational costs, food waste, and inconsistency in product quality, which ultimately affects customer satisfaction and business sustainability. Digital solutions, especially those that support real-time recipe standardization, have the potential to streamline operations, minimize errors, and improve production consistency. This study aims to design and develop an Android-based food recipe management application using Flutter and REST API to support the digital transformation of MSMEs in the culinary sector. The Research and Development (R&D) approach with a prototyping model was applied, involving iterative stages: literature review, needs analysis, interface design using Figma, implementation using Flutter and REST API, and Black Box Testing involving real users for functional evaluation. The results show that all core features login, recipe search, categorization, and recipe data management (add, edit, delete) functioned properly as intended. User feedback indicated increased operational efficiency, reduced manual effort, and improved consistency in recipe handling, particularly in onboarding new staff and ensuring product uniformity. In conclusion, the developed application contributes practically to improving recipe management efficiency and supporting the digital transformation of MSMEs. This system also lays the groundwork for future development of AI-powered features, automatic nutrition analysis, and cross-platform expansion to iOS and web.